(untitled) - Werstein, Irving (New York, 1964)
As the nineteenth century drew to a close, the United States reached the end of its own frontiers. The time had come to find new markets for American products and to enter the global picture as a growing power. At the same time, in Cuba the tyrannical rule of the dying Spanish Empire inflicted incredible cruelties on the Cuban people who were struggling to gain their freedom.
Keywords: United states; History